In Humanized Sickle Cell Mice, Imatinib Protects Against Sickle Cell–Related Injury. Issue 3 (28th March 2023) - Federti, Enrica; Matte, Alessandro; Recchiuti, Antonio; Garello, Francesca; Ghigo, Alessandra; El Nemer, Wassim; Terreno, Enzo; Amoresano, Angela; Mattoscio, Domenico; Turrini, Franco; Lebouef, Christophe; Janin, Anne; et al.
Abstract : Drug repurposing is a valuable strategy for rare diseases. Sickle cell disease (SCD) is a rare hereditary hemolytic anemia accompanied by acute and chronic painful episodes, most often in the context of vaso-occlusive crisis (VOC). Although progress in the knowledge of pathophysiology of SCD have allowed the development of new therapeutic options, a large fraction of patients still exhibits unmet therapeutic needs, with persistence of VOCs and chronic disease progression. Here, we show that imatinib, an oral tyrosine kinase inhibitor developed for the treatment of chronic myelogenous leukemia, acts as multimodal therapy targeting signal transduction pathways involved in the pathogenesis of both anemia and inflammatory vasculopathy of humanized murine model for SCD. In addition, imatinib inhibits the platelet-derived growth factor-B–dependent pathway, interfering with the profibrotic response to hypoxia/reperfusion injury, used to mimic acute VOCs. Our data indicate that imatinib might be considered as possible new therapeutic tool for chronic treatment of SCD. Abstract :